Can BISP be used for Poverty Reduction? - Ahmad, Shahzad (Journal of History Culture and Art Research, 2018)
The overall purpose of this research is to understand the dynamics of the social safety nets (Benazir Income Support Program, BISP) under the present circumstances of Pakistan, the role in the economy, the designing of the program and impact on poverty alleviation. The further the study evaluates if the program BISP has achieved its objectives and analyses its designing, payment mechanism, targeting techniques, the capacity and quality of the organization. This research implements a mix of qualitative and quantitative techniques. For the quantitative part, the researcher conducted a field study to collect data. The specific objectives of the study may be summarized as to make a thorough review of different social safety nets being run in different countries across the globe with special reference to Pakistan; to analyse the benefits of the program and to see how these could be maximized; and to find out the gaps in the current social safety net program (BISP) and to improve it through provisioning of policy measures and recommendations.